Consumo e mídia na formação em dança: o papel do culto ao corpo na cena contemporânea - Kliemann, Gisele (2009)
The last century (XX) developed a new concept of the body that conquered a new space for its representation. The association between aesthetic and beauty brought relevance to the physical formof the body and promoted what it is being called cult to the body that is here understood as the relations and interventions around beauty that are socially idealized. The media became the efficient agent in the supervaluation of the corporal appearance and in the promotion of a constant search of an ideal body. Standardized by the values of the consumption society, he body turned itself in a body-involucre, in a body-packing. All that counts is appearance. The media stirs us up to desire this body and all the activities needed to approach it. The media spread the need for permanently improving, remodeling, reshaping the stops body. Media keep us desiring the desire of this body. Inserted in this context, the contemporary dance suffers consequences of this process in what concerns to the formation of its dancers, although not investing in only one aesthetic standard of the body. Contemporary dance sees in its dancers the action of consumerism. Dancers become eager consumers of techniques and trainings believing that they will be able to dance all types of dance. The thesis is dedicated to identify what produces thie new statement of the body, identifying the media as the central protagonist in this process. The hypothesis is that the consumeristic attitude expresses itself in dance as a form of consumption of different techniques of formation. The techniques are transformed into merchandises and the desire becomes the desire to continue to desire a body never reached. The instauration of the body as merchandise brings the need to construct a body proper, capable of being distinctively itself in the collective. The search of this body is regulated by fashion and by the media, in the net of global communication. The theoretical corpus was constituted with the corpomídia theory (KATZ&GREINER) and with theoreticians of the culture who prioritize the studies of the body (COSTA, FOUCAULT, LIPOVETSKY, SANT' ANNA, CASTRO, GARCIA). With the aim of pesent them as illustrations of these questions, three professional dance groups of the city of Curitiba are brought here